Pembentukan Kepribadian Siswa Sekolah Dasar di Era Milenial Melalui Pendidikan Karakter - Handriana Naura Irham; Umi Karimah; Sekar Asti Andini; Selvi Alia Safira; Muhardila Fauziah; Yeni Sulaeman (Universitas Negeri Padang, 2023)
This research was conducted to find out how to form children's personalities through character education in the millennial era and ways to overcome the problems faced by the current generation. Obtaining research data using the literature review method, by identifying, evaluating and synthesizing the results of research conducted by previous researchers and practitioners. Character education is a step to interpret in an effort to observe behaviour based on existing norms. Seeing that in the current era, which is called the millennial era, there are often moral deviations for the nation's children. The results of the identification that the researchers did conclude that moral deviations need improvement by cultivating character values in the nation's children. The goal is that future generations can maintain the personality and culture of the nation. So that the author's assessment of character education in the millennial era plays an important role in the growth and development of children to create a child's personality with character according to the norms that exist in Indonesian society. The conclusion shows that nowadays it is often seen that children's behaviour is out of control or children's attitudes are not in accordance with existing norms and rules.